Meletijo Pigo Dialogo dedikacijos adresatas - Svarevičiūtė, Kristina (Literatūra, 2015)
The dedicatory letter of Meletios Pigas’ Dialogue published in the printing-house of Vilnius Orthodox Holy Trinity brotherhood in 1596, is addressed to Τā ΕΥΓΕΝΕΣΤΑΤā ΚΑΙ ΜΕΓΑΛΟΠΡΕΠΕΙ ΑΡΧΟΝΤΙ ΚΥΡΙā ΙΩΑΝΝ, Τā ΜΕΓΑΛā ΠΡΑΓΜΑΤΕΥΤ. The name of the addressee is not specified, and the term πραγματευτής is polysemantic, and the identity of that person is still not established. He could have been a merchant or a high official. Having evaluated the polysemy of the term, the purpose of the dedication and the circumstances under which the book was published, the conclusion was drawn that πραγματευτής is a high official, and mentioning his name would serve as a protection for the book. The brotherhood traditions of publishing and other Slavonic as well as Greek texts enable to suppose that the Dialogue is dedicated to Chancellor and Hetman of the Great Duchy of Lithuania Jonas Zamoiskis.